Conformity Test of Human Chorionic Gonadotropin (HCG) Test Results Using Immunochromatographic Method between Various Brands - Osni Ilu; Torajasa Achmar; srikitnurkamiden (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Human Chorionic Gonadotropin (HCG) is a hormone produced by the placental tissue in early pregnancy. This hormone is excreted in the urine or when there is an abnormal proliferation of the chorionic epithelial tissue, such as moles or choriocarcinoma. The problem formulation in this study is that there is a match between the results of the HCG examination using the immunochromatographic method on three different brands at the Kabila Health Center, Bone Bolango District. This study aims to determine the suitability of the results of the HCG examination with the Immunochromatographic Method on three different brands. The method in this study used a quantitative approach. The type of data used was primary data in the form of research results and secondary data in the form of data from literature, books and documents. The sampling technique in this study used an accidental sampling technique with a sample of 30 people. From the research that has been conducted on 30 urine samples of pregnant women using three brands of Human Chorionic Gonadotropin (HCG) kits, namely: 1) one med test. 2) medical sterile test. 3) the accurate strip; shows the results that there was no significant difference to the results of the suitability test of HCG using these three brands.